Use of a hand-worn accelerometer to measure hand differences in Grooved Pegboard Test - Tércio Apolinário-Souza; Marco Antônio Cavalcanti Garcia; Guilherme Menezes Lage; Lucas Eduardo Antunes Bicalho Bicalho; Nathálya Marinho Gardênia de Holanda Nogueira; Flávia Batalha Gomes Costa; Lidiane Aparecida Fernandes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Research on laterality, which pertains to the preference for using one hand over the other in daily activities, has recently been a growing topic of investigation. Studies demonstrate that performance differences between the right and left hands arise from distinct strategies in utilizing information for movement execution. To conduct a more comprehensive analysis of these differences, we aimed to investigate various measures using a wrist accelerometer during the execution of a traditional tool to assess manual performance. The proposed hypothesis suggested that tasks performed with the right hand would exhibit shorter movement times due to more efficient real-time information processing. In contrast, tasks performed with the left hand would show shorter reaction times due to movement planning proficiency. Furthermore, we hypothesized that increased task complexity would make these differences more pronounced. The study revealed that, in the less complex task, the right hand outperformed the left hand in execution speed, whereas the left hand demonstrated faster reaction times in the more complex task. The task complexity highlighted the differences, emphasizing the impact of task demands on hand specialization. Using an accelerometer provided valuable insights, indicating potential avenues for refining assessment tools and analyzing manual control.